Thyroid hormone levels and temperature during development alter thermal tolerance and energetics of Xenopus laevis larvae - Katharina Ruthsatz and Kathrin H. Dausmann and Myron A. Peck and Claudia Drees and Nikita M. Sabatino and Laura I. Becker and Janica Reese and Lisa Hartmann and Julian Glos (Conservation Physiology, 2018)
Environmental variation induced by natural and anthropogenic processes including climate change may threaten species by causing environmental stress. Anuran larvae experiencing environmental stress may display altered thyroid hormone (TH) status with potential implications for physiological traits. Therefore, any capacity to adapt to environmental changes through plastic responses provides a key to determining species vulnerability to environmental variation. We investigated whether developmental temperature (Tdev), altered TH levels and whether the interactive effect of both affect standard metabolic rate (SMR), body condition (BC), survival and thermal tolerance in larvae of the African clawed frog (Xenopus laevis) reared at five temperatures with experimentally altered TH levels. At metamorphosis, SMR, BC and survival were significantly affected by Tdev, TH status and their interaction with the latter often intensified impacts. Larvae developing at warmer temperatures exhibited significantly higher SMRs and BC was reduced at warm Tdev and high TH levels suggesting decreased ability to acclimate to variation in temperature. Accordingly, tadpoles that developed at warm temperatures had higher maximum thermal limits but more narrow thermal tolerance windows. High and low TH levels decreased and increased upper thermal limits, respectively. Thus, when experiencing both warmer temperatures and environmental stress, larvae may be less able to compensate for changes in Tdev. Our results demonstrate that physiological traits in larvae of X. laevis are strongly affected by increased TH levels and warmer temperatures. Altered TH levels and increasing Tdev due to global change may result in a reduced capacity for physiological plasticity. This has far reaching consequences since the energetic requirement at the onset of metamorphosis is known to determine metamorphic success and thus, is indirectly linked to individual fitness in later life stages.
Keywords: Climate change; Metabolic costs; Metamorphosis; Standard metabolic rate (SMR); Thermal tolerance